APPLICATION OF THE RULE OF AL-WUJUH WA AN-NAZHAIR ON TARJAMAH TAFSIRIYAH TO THE WORD HEART IN THE TRANSLATION OF THE MINISTRY OF RELIGIOUS AFFAIRS OF THE REPUBLIC OF INDONESIA - Amien Nur Wicaksono; Sayed Akhyar; Andri Nirwana AN; Mohamed Akhiruddin Bin Ibrahim (Profetika: Jurnal Studi Islam, 2024)
Differences in language usage and translation meanings related to a word in the Qur’an are often confused. For example, as well as the word heart (qalb) in the Qur’an is mentioned 153 times in the singular, double, or plural. Sometimes qalb is interpreted as the meaning of reason knowledge as in the tafsir al-mishbah in QS. Qaf verse 37 interprets that the word qalb means someone who has perfect knowledge. But in the translation of the Qur’an Kemenag, the word qalb in the verse is still interpreted with the heart. This sometimes begs the question of what the verse means. This study used library research. This study compiles and searches for data and theories about the meaning of qalbu translation in the Qur’an on the Qur’an and the translation of the work of the Qur’an Kemenag including books/literature and written works of relevant figures as data sources. This research is qualitative descriptive. The approach used in this study is the theory of interpretation with the maudhu’iy (thematic) method because the collected data will be analyzed with the theory of interpretation with the maudhu’iy method. The results of this research on the latest official website of the Qur’an Kemenag, include an addition of a brief interpretation to express the meaning that the meaning of the heart in translation is a heart that can think and know the truth.